Meeting the bilingual learning needs of Tibetan minority students in Qinghai Province: A multiple perspective investigation into problems and solutions - Shi, Meng; Huang, Jinyan; Lu, Guo (Frontiers in Psychology, 2022)
Using student and teacher open-ended questionnaires, and interviews with teachers and school principals and administrators, this study examined the bilingual learning difficulties faced by the Tibetan minority students in Qinghai Province, China, the challenges in meeting their needs, and the suggestions for coping with these challenges. The participants included 200 Tibetan minority students, 20 classroom teachers, and 10 school principals and administrators randomly selected from eight secondary schools located in eight different counties, where there are the most Tibetan minority students in Qinghai Province. The results showed that they experienced considerable difficulties in both spoken and written Chinese, which had prevented them from understanding the lectures, answering questions, interacting with peers in the classroom, and communicating with friends and classmates outside of classroom. The challenges in meeting their bilingual learning needs include: (a) a language choice dilemma for parents, (b) insufficient training of bilingual education teachers, (c) lack of bilingual education resources; (d) short of qualified teachers; (e) lack of parent-school communication; and (f) insufficient training of principals and administrators. Suggestions for coping with these challenges and educational implications are discussed.